Introducing the International Journal of Information Technology Education - IJITE - Lientz, Ben; Mylonopoulos, Nikos; Ramani, K.V. (Senate Hall Academic Publishing, 2004)
Welcome to the launch issue of the International Journal of Information Technology Education (IJITE). This innovative new journal is devoted to enhancing information technology education worldwide by publishing high quality refereed teaching materials, articles on key developments in teaching methods and technologies, and new institutional frameworks for IT education. The mission of the IJITE is to disseminate leading-edge teaching resources, and research on IT education, in a format that can be readily accessed primarily by teachers and students, but also by the wider audience – in particular managers and industry professionals. The IJITE therefore aims to highly useful and excellent source of course materials as well as pedagogical reviews for those involved in information technology education and related areas. The journal also intends to become a key information resource for managers to keep up to date with the latest developments in the field.